logo

Ask Questions, Get Answers

 
X
 Search
Want to ask us a question? Click here
Browse Questions
Ad
0 votes

General solution of differential equations: $e^y dx+(xe^y-2y)dy=0$

$(a)\;xe^y-y^2=c \\ (b)\;ye^x-x^2=c \\ (c)\;ye^y+x=c \\ (d)\;xe^y-1=cy^2$
Can you answer this question?
 
 

1 Answer

0 votes
$e^ydx+xe^ydy-2ydy=0$
=> $d(xe^y)-d(y^2)=0$
$xe^y=y^2+c$
Hence a is the correct answer.
answered Feb 3, 2014 by meena.p
 

Related questions

Ask Question
student study plans
x
JEE MAIN, CBSE, NEET Mobile and Tablet App
The ultimate mobile app to help you crack your examinations
Get the Android App
...